Pembudayaan Literasi Bahasa Dalam Meningkatkan Minat Baca Siswa Kelas III SDIT Baiturrahman Sepat - Nur Amalia; Faustine Fiona Eka Farah Dewi (Jurnal Elementaria Edukasia, 2023)
The importance of reading for students in carrying out their learning and acquiring knowledge encourages schools to create a literate school environment. Schools are obligated to provide facilities that support a reading literacy culture for students by enhancing their reading willingness. İt is crucial to develop school programs that boost reading interest and cultivate a literacy culture within the school. This research aims to provide an overview of the literacy program at SDIT Baiturrahman Sepat and an explanation of how this program enhances reading interest among third-grade students. The research utilizes a descriptive qualitative approach, with the school principal, third-grade teachers, and library personnel as the subjects. İnterviews, observations, and documentation are the methods employed by the researcher to collect data. The research findings reveal that the literacy activities at SDIT Baiturrahman Sepat have been effectively carried out with guidance from the Ministry of Education and Culture (Kemendikbud). This is evidenced by the school’s program that divides literacy activities into three stages: familiarization, development, and learning. The school endeavors to implement this program to enhance reading interest among the students of SDIT Baiturrahman Sepat. The impacts include students developing a fondness for reading, improved reading abilities, increased self-confidence, and creativity, as well as enhanced student academic achievements.